Proteomic Exploration of Porcine Oocytes During Meiotic Maturation in vitro Using an Accurate TMT-Based Quantitative Approach - Jia, Baoyu; Xiang, Decai; Shao, Qingyong; Hong, Qionghua; Quan, Guobo; Wu, Guoquan (Frontiers in Veterinary Science, 2022)
The dynamic changes in protein expression are well known to be required for oocyte meiotic maturation. Although proteomic analysis has been performed in porcine oocytes during in vitro maturation, there is still no full data because of the technical limitations at that time. Here, a novel tandem mass tag (TMT)-based quantitative approach was used to compare the proteomic profiles of porcine immature and in vitro mature oocytes. The results of our study showed that there were 763 proteins considered with significant difference−450 over-expressed and 313 under-expressed proteins. The GO and KEGG analyses revealed multiple regulatory mechanisms of oocyte nuclear and cytoplasmic maturation such as spindle and chromosome configurations, cytoskeletal reconstruction, epigenetic modifications, energy metabolism, signal transduction and others. In addition, 12 proteins identified with high-confidence peptide and related to oocyte maturation were quantified by a parallel reaction monitoring technique to validate the reliability of TMT results. In conclusion, we provided a detailed proteomics dataset to enrich the understanding of molecular characteristics underlying porcine oocyte maturation in vitro.